2011
DOI: 10.4102/sajip.v37i1.867
|View full text |Cite
|
Sign up to set email alerts
|

Leadership effectiveness in Higher Education: Managerial self-perceptions versus perceptions of others

Abstract: <strong>Orientation:</strong> The study reported here explores the relationship between managerial selfperceptions and perceptions of others (the manager’s direct supervisor, peers and subordinates) with regard to leadership effectiveness (LE) in a group of managers in the context of a South African university undergoing a merging process.<p><strong>Research purpose:</strong> The purpose of this study was to investigate the prevalence of selfperception accuracy amongst the manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The second objective of this study is to evaluate the determinants of product innovation in the tertiary education sector in Malaysia. Nowadays, the tertiary education institutions are highly competitive because of the rapid changes and the stringent policies required in the educational environment, new technology, variety of the academic programs, and the requirement of having higher knowledge management capacity in implementing the transformation process in the tertiary education sector (Herbst & Conradie, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The second objective of this study is to evaluate the determinants of product innovation in the tertiary education sector in Malaysia. Nowadays, the tertiary education institutions are highly competitive because of the rapid changes and the stringent policies required in the educational environment, new technology, variety of the academic programs, and the requirement of having higher knowledge management capacity in implementing the transformation process in the tertiary education sector (Herbst & Conradie, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on leadership have shown mixed results regarding the significance of differences between self-evaluation and evaluation by observers. Even though observers' average rating tends to be higher (better) than leaders' self-rating, mean values were found to lie within one standard deviation of the normal distribution (Herbst & Conradie, 2011;Posner, 2016). Importantly, no such comparative studies are known regarding an event-related change of leadership style.…”
Section: Hypotheses Developmentmentioning
confidence: 80%
“…Different leadership styles may affect organisational effectiveness or performance. As there is a widespread acceptance that there is a need for effective leadership in higher education to shape institutional reform and transformation, we have noticed an increase in the rethinking of leadership practices in higher education (Herbst & Conradie, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%